Addressing Violence Against Parents and Peers and Violence in Schools Through the Perspective of Ecological Theory - Monika Klun; Danijela Frangež; Aleš Bučar Ručman (Center for Educational Policy Studies Journal)
This paper examines violence against parents and peers and violence in schools using Bronfenbrenner’s ecological system theory. We aim to establish connections between these forms of violence, perpetrator characteristics, and conclusions about the influences at different ecological layers. Through in-depth empirical research, we reviewed police, prosecutorial, and court files on child-parent violent crimes. Out of the total closed cases, 46 were included for further analysis, with nine cases addressing violence or misconduct in schools. Our findings highlight the link between violence against parents, early adolescent misbehaviour, and academic problems. Outward manifestations of these issues include discipline problems, truancy, association with problematic peers, substance abuse or addiction, and violent behaviour. Boys exhibit a progression from psychological to physical abuse against their parents and others. These results confirm other conclusions on the early onset and persistent nature of violent and delinquent behaviour. Notably, mental health issues and substance abuse play a significant role at the microsystem level. In conclusion, we recommend policy upgrades with a systematic approach to address youth violence, appropriate care of young people’s mental health and the public delegitimation of various forms of violence.